2012
DOI: 10.2147/jpr.s35108
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesic activity of nucleoside transport inhibitors in models of inflammatory pain in guinea pigs

Abstract: Background and methodsThe role of the endogenous purine nucleoside, adenosine, in nociception is well established. Inhibition of the equilibrative nucleoside transporter (ENT1) prevents adenosine uptake into cells, and could therefore enhance the antinociceptive properties of adenosine. The effects of ENT1 inhibition were studied in two animal models of inflammatory pain. Analgesic activity was assessed in a complete Freund’s adjuvant (CFA)-induced and carrageenan-induced mechanical and thermal hyperalgesia mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…We identified a compound known as soluflazine that has been demonstrated to have 20-to 100-fold increased specificity for ENT2 relative to ENT1 in vitro (49)(50)(51). In vivo studies demonstrate that soluflazine is efficacious via increasing extracellular adenosine (77). Continuous delivery of soluflazine mimicked the protective effect observed with dipyridamole treatment in murine colitis.…”
Section: Figure 9 Genetic or Pharmacologic Ent2 Inhibition Does Not mentioning
confidence: 83%
“…We identified a compound known as soluflazine that has been demonstrated to have 20-to 100-fold increased specificity for ENT2 relative to ENT1 in vitro (49)(50)(51). In vivo studies demonstrate that soluflazine is efficacious via increasing extracellular adenosine (77). Continuous delivery of soluflazine mimicked the protective effect observed with dipyridamole treatment in murine colitis.…”
Section: Figure 9 Genetic or Pharmacologic Ent2 Inhibition Does Not mentioning
confidence: 83%
“…in various inflammatory pain models (Maes et al 2012). In addition, adenosine also mediates the analgesic mechanism of acupunctures via peripheral A1 receptors (Goldman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Maes et al demonstrated that systemic administration of ENT-1 inhibitors can reverse hyperalgesia in guinea pig inflammatory pain models [ 188 ]. The mechanism underlying this analgesia seems to be the blocking of adenosine reuptake into cells, allowing greater activation of A 1 and A 2 AR [ 188 ]. These results show that it is necessary to investigate the potential therapeutic effect of ENT inhibition.…”
Section: Perspectives Of Atp and Adenosine Signaling Modulation: Pmentioning
confidence: 99%